A Comparative Analysis of Descartes’ and Spinoza’s Notions of Intuition - Elias Ifeanyi Uzoigwe (dialektika kontemporer, 2021)
This study aims at Comparatively Analysing Descartes’ and Spinoza’s Notions of Intuition. The rationalists employ logico-mathematico (logical and mathematical) model as the foundation of their epistemological pursuit, while the empiricists in opposition to the rationalists hold that knowledge is derived from sense experience. Because the rationalists are in unism in their argument against the empiricists and vice versa; it is important to note that there are variations in their approaches to those features they have in common. However, the rationalists among other things based their argument and judgement on intuition as a clear, certain and reliable strand of cognition. It is their conviction that only a living being can think, and so, they conceive intuition as an authentic and most certain route to knowledge. The variation in their arguments to uphold intuition as their common feature is what this work describes as epistemic sustainability. These scholars’ variegated position on one issue brings about new insight, creativity and productivity within the epistemic circle. It shows that epistemology is on-going, interesting and indeed, a continuous process. This study employed analytic, historical, textual and contextual methods of research.